Optimal search strategy for clinical trials in the Latin American and Caribbean Health Science Literature Database (LILACS) - Castro, Aldemar Araujo; Clark, Otávio Augusto Câmara; Atallah, Alvaro Nagib (São Paulo Medical Journal, 1997)
OBJECTIVE: To define and disseminate the optimal search strategy for clinical trials in the Latin American and Caribbean Health Science Literature (LILACS). This strategy was elaborated based on the optimal search strategy for MEDLINE recommended by Cochrane Collaboration for the identification of clinical trials in electronic databases. DESIGN: Technical information. SETTING: Clinical Trials and Meta-Analysis Unit, Federal University of São Paulo, in conjunction with the Brazilian Cochrane Center, São Paulo, Brazil. (http://www.epm.br/cochrane). DATA: LILACS/CD-ROM (Latin American and Caribbean Health Science Information Database), 27th edition, January 1997, edited by BIREME (Latin American and Caribbean Health Science Information Center). LILACS Indexes 670 journals in the region, with abstracts in English, Portuguese or Spanish; only 41 overlap in the MEDLINE-EMBASE. Of the 168.902 citations since 1982, 104,016 are in human trials, and 38,261 citations are potentiality clinical trials. Search strategy was elaborated combining headings with text word in three languages, adapting the interface of the LILACS. We will be working by locating clinical trials in LILACS for Cochrane Controlled Trials Database. This effort is being coordinated by the Brazilian Cochrane Center.